Hengniu: Fast Bearing and High Yielding Coconut Varieties - Novarianto, Hengky; Tulalo, Meity A.; Mawardi, Sukmawati; Mahayu, Weda Makarti (International Coconut Community, 2024)
Benefits of coconut varieties that stakeholders want are early bearing, high yielding, short stems, and slow growth for height. Most local tall coconut palms in Indonesia have stem height above 20 m, making it increasingly difficult to climb to harvest fruit or tapping sap thereby making the harvesting cost high. To breed varieties of desired characters, an evaluation trial was initiated in 2014 with BYD x MTT-S4, RAD x MTT-S4, and KHINA-1 as a control. The crossing was done in 2012 and seedlings planted in January 2014 at Mapanget Experimental Garden, Indonesian Palma Crops Research Institute, North Sulawesi. The study used a Randomized Block Design (RBD) of three types of coconut hybrids, four replications with a plot size of 16 trees. Morphological observations were carried out on stem, crown and leaf characters, inflorescences and flowers, nut production, fruit components, copra, oil content, and fatty acid composition. The results of ANOVA analysis and statistical tests obtained those vegetative characters, such as stem circumference and number of leaf, generative characters namely the number of bunches, first flowering, and fruit production of these three crosses at the age of 4 years after planting, did not show a significant difference. The first initial flowering was in the coconut hybrid of RBD x MTT-S4, which is 26 months, followed by BYD x MTT-S4 in 32 months and KHINA-1 in 36 months after planting. The results of the analysis of fruit and copra production at the age of 5 years showed a significant increase between hybrid coconuts. The highest to lowest fruit production was obtained in BYD x MTT-S4 hybrid coconut, RBD x MTT-S4, KHINA-1, which were 64 nuts, 44 nuts and 26 nuts /palm respectively, or estimated copra production was 2.26 tons, 1.45 tons and 0.88 tons copra/ha. At 6 years old the harvest of fruits from the three hybrid coconuts is obtained sequentially 118 nuts, 99 nuts and 94 nuts/palm. While estimation of copra yield per hectare is found the highest in BYD x MTT-S4 hybrid coconut is 3.86 ton/ha/year and this yield differently significant compare with RBD x MTT-S4 is found 3.04 ton/ha/year, and control hybrid of KHINA-1, which is about 2.74 ton/ha/year. Based on the production potential, hence the estimated optimum production when aged over 10 years can reach more than 5 tons/ha/year. The hybrid coconut variety BYD x MTT-S4 is released in October 2019 under the name HENGNIU.